Book Review: P. A. GIANNOPOULOS - A. G.K. SAVVIDES, Μεσαιωνική Πελοπόννησος. Βυζάντιο, Λατινοκρατία, Πρώιμη Τουρκοκρατία, Herodotos Publications, Athens, 2013, pp. 610, ISBN 978-960-485-048-8 - LEONTSINI, Maria (Byzantina Symmeikta, 2015)
Book Review:P. A. Giannopoulos - A. G.K. Savvides, Μεσαιωνική Πελοπόννησος. Βυζάντιο, Λατινοκρατία, Πρώιμη Τουρκοκρατία, Herodotos Publications, Athens, 2013, pp. 610, ISBN 978-960-485-048-8